Setting the evolutionary timeline: Tillandsia landbeckii in the chilean atacama desert - Möbus, Johanna; Kiefer, Christiane; Quandt, Dietmar; Barfuss, Michael H.; Koch, Marcus (Plant systematics and evolution, 2021)
The Chilean Atacama Desert is among the oldest deserts of the world. Here, Tillandsia landbeckii is forming a unique vegetation type known as Tillandsia lomas. This vegetation consists in its typical configuration of one single vascular plant species only and forms regular linear structures in a sloped landscape and is largely depending on fog occurrence as dominant source of water supply. Without developing a typical root system, there are only few other terrestrial Tillandsia species growing on bare sand in Chile and Peru such as T. marconae, T. virescens, T. purpureaor T. latifolia. Although phylogenetic evidence is limited, convergent evolution of this unique growth behavior is evident. The predominantly arid and hyper-arid climate exists since the Early Miocene, which raises the question about timing of T. landbeckii evolutionary history. Phylogenomic analyses using whole plastome sequence data highlight the onset of diversification in T. landbeckii approximately 500,000 years ago. We also demonstrate subsequent secondary genetic contact with T. purpurea during the Late Pleistocene using DNA sequence data and genome size estimates, which resulted into the formation of T. marconae.